Understanding the Implications of Peer Support for Families of Children With Neurodevelopmental and Intellectual Disabilities: A Scoping Review - Chakraborti, Michelle; Gitimoghaddam, Mojgan; McKellin, William H.; Miller, Anton Rodney; Collet, Jean-Paul (Frontiers in Public Health, 2021)
Background: Families are involved in day-to-day caregiving of children with neurodevelopmental and intellectual disabilities (NDID). Given the increasing prevalence of children with NDID and impact of family caregiving on psychological, social, and economic implications for both the child and family, understanding and supporting these families is an important public health concern. Objective: We conducted a scoping review on peer support networks to understand implications on families. Considering increasing prevalence of NDID’s, understanding the implications of existing networks is critical to improve future support networks that complement and reduce the burden on existing formal support systems. Design: A comprehensive search of multiple databases was involved. Articles were screened by two reviewers Any disagreements were resolved by a third reviewer. We explored existing research on parent-to-parent peer support networks, that developed informally as well as those that involved a formal facilitator for the group interpersonal processes. There were no limits on study design, date and setting of the articles. We included all research studies in English that included an identifier for (i) ‘peer support networks’, (ii) ‘children with neurodevelopmental and intellectual disabilities’ and (iii) ‘family caregiver outcomes’. RESULTS: We identified 36 articles. Majority studies were conducted in North America, and were face to face networks. They included families of children with a wide range of NDIDs. Relevant information extracted from different studies highlighted peer support network characteristics and development process, needs of family caregivers attending these networks, factors affecting caregiver participation and the impact of peer support networks on family caregivers. These networks represent a way to strengthen family caregivers, developing resilience and social interactions. Family caregivers sharing similar experiences support one another and provide critical information to each other. Although results are encouraging, future studies incorporating improved study designs are needed to better evaluate the effectiveness of peer support networks. Furthermore, studies where peer support networks develop organically while the child is supported are warranted. CONCLUSION: Although the results obtained are encouraging for families, our findings support the need for further research studies of peer support networks with better designs and more detailed description of the factors involved in the development.